2007
DOI: 10.1007/s11747-007-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

The ad creativity cube: conceptualization and initial validation

Abstract: Advertising creativity is conceptualized as a function of three dimensions-novelty, meaningfulness, and connectedness. Novelty and meaningfulness involve infocentric aspects, while connectedness incorporates the perspective of the audience. The relationship among these dimensions and ad effectiveness, and the linkage of ad creativity level to persuasion is then posited. Two experiments were conducted among 201 undergraduates. The first tested novelty and meaningfulness; while the second tested connectedness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
131
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 28 publications
11
131
2
2
Order By: Relevance
“…Information content in ads can increase their attractiveness and persuasiveness. Much of the advertising literature has claimed that the fundamental role of advertising is to communicate this type of information and that creativity and the entertainment aspect of the ad is used mainly to enhance the communication process (e.g., see Ang et al 2007). …”
Section: The Role Of Entertainment In Advertisingmentioning
confidence: 99%
See 1 more Smart Citation
“…Information content in ads can increase their attractiveness and persuasiveness. Much of the advertising literature has claimed that the fundamental role of advertising is to communicate this type of information and that creativity and the entertainment aspect of the ad is used mainly to enhance the communication process (e.g., see Ang et al 2007). …”
Section: The Role Of Entertainment In Advertisingmentioning
confidence: 99%
“…Research has shown that creative ads get more attention and stand out (Ang et al 2007, Smith et al 2007). …”
Section: Entertainment and Ad Attractivenessmentioning
confidence: 99%
“…Advertising practitioners consider creativity as a solution of breaking through the greater media clutter (e.g. Ang, Leong and Lee, 2007;Pieters, Warlop and Wedel, 2002). As a result, marketers are now turning towards demanding more novel and creative advertisements for their advertising campaign (Ang et.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2007). In this sense, creative advertisements are considered as an effective tool to break through the media clutter, reach to consumer's minds, build an impression and lead to greater effectiveness of the campaign (Ang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation